Safety And Occupational Risks Among Red Crescent Paramedics: A Systematic Review Of Injuries, Stress, And Preventive Strategies (2015–2025) (The Review of Diabetic Studies, 2025)
Background: Paramedics working within Red Crescent systems operate in unpredictable, high-pressure environments that place them at elevated risk of physical and psychosocial harm. Despite growing global attention to the occupational health of emergency medical services (EMS) personnel, limited research has synthesized the unique hazards faced by Red Crescent paramedics.Objective: This systematic review synthesizes evidence published between 2015 and 2025 on occupational injuries, psychosocial risks, and preventive strategies among paramedics working in Red Crescent and comparable EMS systems.Methods: A PRISMA-aligned search was conducted in PubMed, Scopus, Web of Science, EMBASE, CINAHL, and Google Scholar. Eligible studies included cross-sectional, cohort, case–control, qualitative, interventional designs, and systematic reviews addressing musculoskeletal disorders (MSDs), needle-stick injuries (NSIs), workplace violence, stress, burnout, fatigue, sleep disturbances, or preventive strategies. Data extraction and quality appraisal were performed using standardized JBI tools. Findings were synthesized narratively due to methodological heterogeneity.New Microsoft Word DocumentResults: Thirty-seven studies met the inclusion criteria. MSDs were the most prevalent occupational injuries, affecting 48%–78% of paramedics, with low-back pain as the primary complaint. NSI prevalence ranged from 9%–28%, with under-reporting identified as a major barrier to safety surveillance. Workplace violence was widespread, with 55%–70% reporting verbal aggression and 8%–19% reporting physical assault. Psychosocial risks—including chronic stress, burnout (21%–56%), and sleep disturbances (38%–62%)—were consistently high across Red Crescent settings. Effective preventive measures identified in the literature included ergonomic interventions (e.g., powered stretchers), infection-control training, de-escalation training, peer-support programs, and organizational improvements; however, implementation remains inconsistent across regions.Conclusion: Red Crescent paramedics face substantial occupational hazards that threaten both workforce well-being and the quality of prehospital emergency care. Despite the availability of evidence-based preventive strategies, adoption remains uneven. Strengthening ergonomic support, enhancing safety culture, expanding training programs, and providing structured mental-health services are essential to improving workforce resilience and patient safety.Implications: Findings highlight the urgent need for standardized safety frameworks across Red Crescent systems, targeted interventions addressing both physical and psychosocial risks, and further research evaluating long-term and interventional outcomes.